Runners Employ Different Strategies to Cope With Increased Speeds Based on Their Initial Strike Patterns - Ekizos, Antonis; Santuz, Alessandro; Arampatzis, Adamantios (Frontiers in Physiology, 2021)
In this paper we examined how runners with different initial foot strike pattern (FSP) develop their pattern over increasing speeds. The foot strike index (FSI) of 47 runners (66% initially RFS) was measured in six speeds (2.5 – 5.0 m/s), with the hypotheses that the FSI would increase (i.e. move towards the fore of the foot) in RFS strikers, but remain similar in MFS runners. The majority of runners (77%) maintained their original FSP by increasing speed. However, we detected a significant (16.8%) decrease in the FSI in the MFS group as a function of running speed, showing changes in the running strategy, despite the absence of a shift from one FSP to another. Further, while both groups showed a decrease in contact times, we found a group by speed interaction (p<0.001) and specifically that this decrease was lower in the MFS group with increasing running speeds. This could have implications in the metabolic energy consumption for MFS-runners, typically measured in low speeds for the assessment of running economy.